Myth – Archaic Jejune Science оr Factor оf Life? - Stelmokas, Saulius (Problemos, 2004)
Contemporary science considers the myth as a jejune knowledge, specific for a primitive man. Science has replaced myth in our life, taking myth’s place. Irrespective of this science opinion, myth is working in our world like it was working in our ancestors’ life. Scientific knowledge doesn’t govern our life – it is not true to life. Scientific truth is just theorical truth. Myth always is practical – it is message – imperative, it is pushing us to act. Because of the nature of action, the criterion of truth is inapplicable to myth – the only criterion of myth can be efficacy.